Implementasi Nilai-Nilai Kearifan Lokal Masyarakat Ngata Toro Dalam Membangun Literasi Ekologi Pada Siswa SMAN 5 SIGI - Zumrotin Nisa'; Rendra Zainal Maliki; Suwarni Suwarni; Safirah Nur Alya; Raehan Raehan (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2006)
This study aims to implement the values of local wisdom of the Ngata Toro community in developing ecological literacy among students at SMAN 5 Sigi. The study employed a quantitative approach using a quasi-experimental design, namely an untreated control group design with dependent pretest and posttest samples. The research population consisted of Class XI IPS 1 with 30 students as the experimental group and Class XI IPS 2 with 28 students as the control group. The research instrument was a multiple-choice test consisting of 20 items. The results of hypothesis testing (t-test) using IBM SPSS version 20 indicated that the mean posttest score of the experimental group was 79.17, while that of the control group was 60.18. The obtained Sig. (2-tailed) value was 0.001, which is lower than 0.05 (Sig. 0.001 < 0.05), indicating that H₀ was rejected and Hₐ was accepted. It can be concluded that the implementation of the local wisdom values of the Ngata Toro community has a significant effect on improving ecological literacy among students at SMAN 5 Sigi.